Assessing anxiety symptoms and Traumatic Event Scale scores among medical staff during the COVID-19 pandemic in Colombia: a descriptive cohort study in Bogotá - Pablo Vásquez-Hoyos; Jhon Camacho-Cruz; Sara Marcela Torres Ayala; Susan Tatiana Cárdenas Rojas; Carolina Alexandra Zambrano Pérez; Juanita Yolanda Atuesta-Fajardo; Licet Villamizar-Gómez (BMJ Public Health)
Objective This study aims to assess anxiety and suffering symptoms amid the pandemic, determine factors linked to physicians’ anxiety with COVID-19 patients and describe symptom progression in the initial year of follow-up.Methods Descriptive cohort study involving general practitioners, specialists and interns in the city of Bogotá. The Zung Anxiety Scale and the Traumatic Event Scale (TES) were employed and completed four times during the pandemic. A sample of 558 participants was taken. Physicians with prior diagnoses of psychiatric disorders were excluded. Bivariate tests and a logistic regression model were used.Results Some 7.3% of respondents had anxiety symptoms during the first survey (29/397 physicians) with a clinically significant impact of the traumatic event on 279 of the 397 (70%). Female gender (p=0.04), comorbidities (p=0.01), use of surgical gown (protective, p=0.01), perception of negative thoughts on the part of society (p=0.05), thoughts of wanting to give up or death (p<0.001) and presenting some clinical level of traumatic event impact (p<0.001) were associated with these anxiety symptoms. The multivariate model associated thoughts of quitting (OR 4.55; 95% CI 1.8 to 11.6) and the clinically significant level of TES (OR 7.8; 95% CI 1.0 to 62.5) with anxiety symptoms and the use of a surgical gown as a personal protection element (OR 0.222; 95% CI 0.12 to 0.73; p=0.009) with the protective factor.Conclusions The pandemic significantly impacted Bogota physicians, with around 7.3% of exhibiting anxiety symptoms during the initial assessment. This traumatic experience had a clinically significant effect on 70% of respondents. Over time, anxiety symptoms diminished. Addressing post-traumatic stress phenomena is crucial in similar scenarios to alleviate the impact on healthcare personnel’s anxiety.